A Narrative Review of Diabetes Intervention Studies to Explore Diabetes Care Opportunities for Pharmacists - Shamala Ayadurai; H. Laetitia Hattingh; Lisa B. G. Tee; Siti Norlina Md Said (Journal of Diabetes Research)
Background. We conducted a review of current diabetes intervention studies in type 2 diabetes and identified opportunities for pharmacists to deliver quality diabetes care. Methods. A search on randomised controlled trials (RCT) on diabetes management by healthcare professionals including pharmacists published between 2010 and 2015 was conducted. Results and Discussion. Diabetes management includes multifactorial intervention which includes seven factors as outlined in diabetes guidelines, namely, glycaemic, cholesterol and blood pressure control, medication, lifestyle, education, and cardiovascular risk factors. Most studies do not provide evidence that the intervention methods used included all seven factors with exception of three RCT which indicated HbA1c (glycated hemoglobin) reduction range of 0.5% to 1.8%. The varied HbA1C reduction suggests a lack of standardised and consistent approach to diabetes care. Furthermore, the duration of most studies was from one month to two years; therefore long term outcomes could not be established. Conclusion. Although pharmacists’ contribution towards improving clinical outcomes of diabetes patients was well documented, the methods used to deliver structured, consistent evidence-based care were not clearly stipulated. Therefore, approaches to achieving long term continuity of care are uncertain. An intervention strategy that encompass all seven evidence-based factors will be useful.